ACADEMIC IDENTIFICATION OF CHILDREN WITH SPECIAL NEEDS THROUGH INDIVIDUAL LEARNING PROGRAMS IN INCLUSIVE EDUCATION SCHOOLS IN MAJALENGKA REGENCY - Septiaji, Aji; Rahmawati, Ima Siti (Jurnal Visipena, 2025)
Pendidikan inklusif bertujuan untuk memberikan kesempatan belajar yang setara bagi semua anak, termasuk anak berkebutuhan khusus (ABK). Salah satu aspek penting dalam Pendidikan inklusif adalah identifikasi akademik yang bertujuan untuk memahami kebutuhan belajar ABK guna merancang Program Pembelajaran Individual (PPI) yang sesuai. Dalam praktiknya, banyak sekolah dasar penyelenggara pendidikan inklusi masih menghadapi tantangan dalam mengidentifikasi akademik siswa ABK secara optimal sehingga bisa ditemukan solusi atas permasalahan tersebut. Oleh karena itu, penelitian ini secara masif mengkaji bagaimana identifikasi akademik dilakukan di sekolah dasar inklusif serta bagaimana implementasi PPI dapat membantu meningkatkan perkembangan akademik ABK. Dengan sistem identifikasi yang baik diharapkan setiap siswa ABK mendapatkan pendidikan yang sesuai dengan potensi dan kebutuhannya. Metode penelitian ini menggunakan kualitatif dengan pendekatan studi kasus. Tujuan penelitian ini ialah untuk mengetahui masalah akademik dan strategi akademik terhadap anak berkebutuhan khusus melalui program pembelajaran individual di sekolah penyelenggara pendidikan inklusi. Hasil penelitian menunjukkan bahwa mayoritas siswa mengalami hambatan pada kemampuan literasi, numerasi, koordinasi motorik, dan adaptasi perilaku dengan kecenderungan gaya belajar visual. Program Pembelajaran Individual yang berbasis media visual, metode konkret, aktivitas kinestetik, serta dukungan sosial-emosional terbukti efektif dalam meningkatkan keterampilan akademik dan adaptasi sosial siswa sebab berbasis pada kebutuhan individual, penggunaan media pembelajaran adaptif, latihan psikomotorik terstruktur, pendekatan sosial-emosional yang intensif serta pelatihan guru dalam pendidikan inklusif. Inclusive education aims to provide equal learning opportunities for all children, including children with special needs. One important aspect of inclusive education is academic identification, which aims to understand the learning needs of children with disabilities in order to design an appropriate individualized learning program. In practice, many primary schools offering inclusive education still face challenges in optimally identifying the academic needs of children with disabilities so that solutions can be found. Therefore, this study examines how academic identification is carried out in inclusive primary schools and how the implementation of PPI can help improve the academic development of children with disabilities. With a good identification system, it is hoped that each student with disabilities will receive an education that suits their potential and needs. This research method uses qualitative with a case study approach. The purpose of this research is to find out the academic problems and academic strategies for children with special needs through individualized learning programs in schools that provide inclusive education. The results showed that the majority of students experienced barriers in literacy, numeracy, motor coordination, and behavioral adaptation with visual learning style tendencies. Individualized learning programs based on visual media, concrete methods, kinesthetic activities, and social-emotional support proved effective in improving students' academic skills and social adaptation because they are based on individual needs, the use of adaptive learning media, structured psychomotor exercises, intensive social-emotional approaches and teacher training in inclusive education.